Cropland expansion and grassland loss in the eastern Dakotas: New insights from a farm-level survey. (April 2017) - Wimberly, Michael C.; Janssen, Larry L.; Hennessy, David A.; Luri, Moses; Chowdhury, Niaz M.; Feng, Hongli
Abstract: The western Corn Belt region of the United States has become a hotspot for agricultural extensification and consequent land use and land cover changes. The goals of this research were to characterize geographic patterns of grassland loss resulting from cropland expansion in the eastern Dakotas, and to understand how these changes were associated with characteristics of individual farms and farm operators. We collected data on grassland conversion and other land use decisions through a mail survey of farm operators in North and South Dakota. Overall, 40% of respondents converted at least some grassland to cropland between 2004 and 2014, and the total acreage of converted grassland was equivalent to 5.1% of the surveyed farm acreage. Although most converted grassland acres (3.2% of farm acreage) were from land enrolled in the conservation reserve program (CRP), there were also substantial amounts of native grassland conversion (1.0%) and tame grassland conversion (0.9%). The total acreage of grassland conversion was more than four times larger than the acreage enrolled in CRP and other conservation programs. Different types of grassland conversion (e.g., native grassland versus CRP) were concentrated in different parts of the study region, and were spatially disjunct from the areas of highest conservation program enrollment. Larger farms were more likely than smaller farms to expand their cropland acreage and accounted for a disproportionate share of grassland conversion. Younger farm operators, higher levels of farm income, higher proportions of rented croplands, and marginal yields were also associated with cropland expansion and grassland conversion. Although CRP and other land retirement programs will remain important policy mechanisms for conservation in this region, they are not sufficient to maintain current levels of grassland cover and do not provide protection for native grasslands. Alternative conservation strategies and new agricultural policies are thus critically needed to maintain the ecosystem services provided by grasslands.